Tantangan dan Solusi: Penerapan Model Pembelajaran Discovery Learning dalam Pembelajaran Seni Budaya di Sekolah Menengah Kejuruan - Sukreni, Desak Nyoman; Wiguna, Ida Bagus Alit Arta; Laksana, I Nengah Pandu Dwi (Widya Sundaram : Jurnal Pendidikan Seni Dan Budaya, 2024)
This study examines the application of the discovery learning model in cultural arts learning at Vocational High Schools (SMK) as well as the challenges and solutions faced. Using a qualitative approach and case study design at SMK Negeri 5 Mataram, data were collected through observation, interviews and documentation. The results showed that discovery learning was able to increase students' engagement and creativity. However, limited learning time, minimal facilities, and teachers' lack of understanding of this model are the main obstacles. In addition, students' different cultural backgrounds affect the effectiveness of discovery learning in art learning. Proposed solutions include improved teacher training, adaptation of cultural arts contexts, utilization of digital media, and collaboration with arts communities. This research makes a novel contribution by highlighting the importance of time flexibility, differentiation of student guidance, and creative process-based evaluation in discovery learning. The findings provide practical guidance for the development of more effective cultural arts learning in SMK.